Mindfulness-based therapy for insomnia for older adults with sleep difficulties: a randomized clinical trial. Issue 3 (1st February 2023) - Perini, Francesca; Wong, Kian Foong; Lin, Jia; Hassirim, Zuriel; Ong, Ju Lynn; Lo, June; Ong, Jason C.; Doshi, Kinjal; Lim, Julian
Abstract: Objective: Poor sleep is a modifiable risk factor for multiple disorders. Frontline treatments (e.g. cognitive-behavioral therapy for insomnia) have limitations, prompting a search for alternative approaches. Here, we compare manualized Mindfulness-Based Therapy for Insomnia (MBTI) with a Sleep Hygiene, Education, and Exercise Program (SHEEP) in improving subjective and objective sleep outcomes in older adults. Methods: We conducted a single-site, parallel-arm trial, with blinded assessments collected at baseline, post-intervention and 6-months follow-up. We randomized 127 participants aged 50–80, with a Pittsburgh Sleep Quality Index (PSQI) score ⩾5, to either MBTI ( n = 65) or SHEEP ( n = 62), both 2 hr weekly group sessions lasting 8 weeks. Primary outcomes included PSQI and Insomnia Severity Index, and actigraphy- and polysomnography-measured sleep onset latency (SOL) and wake after sleep onset (WASO). Results: Intention-to-treat analysis showed reductions in insomnia severity in both groups [MBTI: Cohen's effect size d = −1.27, 95% confidence interval (CI) −1.61 to −0.89; SHEEP: d = −0.69, 95% CI −0.96 to −0.43], with significantly greater improvement in MBTI. Sleep quality improved equivalently in both groups (MBTI: d = −1.19; SHEEP: d = −1.02). No significant interaction effects were observed in objective sleep measures. However, only MBTI had reduced WASOactigraphy (MBTI: d = −0.30; SHEEP: d = 0.02), SOLactigraphy (MBTI: d = −0.25; SHEEP: d = −0.09), and WASOPSG (MBTI: d = −0.26; SHEEP ( d = −0.18). There was no change in SOLPSG . No participants withdrew because of adverse effects. Conclusions: MBTI is effective at improving subjective and objective sleep quality in older adults, and could be a valid alternative for persons who have failed or do not have access to standard frontline therapies.